2016
DOI: 10.1007/s13246-016-0445-y
|View full text |Cite
|
Sign up to set email alerts
|

Reducing absorbed dose to eye lenses in head CT examinations: the effect of bismuth shielding

Abstract: The eye lens is considered to be among the most radiosensitive human tissues. Brain CT scans may unnecessarily expose it to radiation even if the area of clinical interest is far from the eyes. The aim of this study is to implement a bismuth eye lens shielding system for Head-CT acquisitions in these cases. The study is focused on the assessment of the dosimetric characteristics of the shielding system as well as on its effect on image quality. The shielding system was tested in two set-ups which differ for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Another recent study investigating the effects of bismuth for eye shielding during brain CT scans demonstrated a 21% to 29% dose reduction to the lens of the eye, with no negative effect on CT image quality. 7 Identically, Hopper and colleagues reported radiation dosage reduction of up to 50% when bismuth-coated latex shielding of the eye is used during cranial CT. 30 A similar study concerning breast and thyroid shielding during chest CT scans recorded a 30% and 50% dose reduction, respectively. 31 Other studies have similarly corroborated significant dose reduction due to shielding techniques.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another recent study investigating the effects of bismuth for eye shielding during brain CT scans demonstrated a 21% to 29% dose reduction to the lens of the eye, with no negative effect on CT image quality. 7 Identically, Hopper and colleagues reported radiation dosage reduction of up to 50% when bismuth-coated latex shielding of the eye is used during cranial CT. 30 A similar study concerning breast and thyroid shielding during chest CT scans recorded a 30% and 50% dose reduction, respectively. 31 Other studies have similarly corroborated significant dose reduction due to shielding techniques.…”
Section: Discussionmentioning
confidence: 99%
“…32 Some studies have indicated an increase in image noise in the area directly underlying the protective shield 31,33,34 ; in contrast, other studies indicate no significant effect on diagnostic image quality. 7,8,35 Radiation shields can be placed either over the area being studied and thus in the path of the radiation beam (i.e., ''in-plane'' shielding), or placed over areas outside of the …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The radiation dose was reduced by about 60% at the top of the CT dose index phantom at each tube current. For comparison, Ciarmatori et al (16) reported that B-shielding can reduce the entrance surface dose by 21%-29% during head CT examinations and Wang et al (17) reported that a B-shield and tube current modulation reduced the radiation dose to the eye lens by 26.4%. Our results are essentially consistent with these previous findings, but the dose reduction was significantly greater during CT imaging in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This study is relevant because the rat radiation cataract model is similar to the human lens opacification. Recently, the investigation conducted by Ciarmatori (2016), for instance, aimed to assess the effect of a bismuth shielding system applied to this organ and its effect on image quality, since a head CT scan can expose it to an unnecessary radiation, even when the region of interest is far from the eyes. This study was performed by stablishing a reference set up without shielding and dose reduction was assessed by placing TLD on the eye lenses of an anthropomorphic phantom.…”
Section: Head/head and Neck: Cirs Atom Phantom And Rando Phantommentioning
confidence: 99%